4-Amino-3-(p-tolyloxymethyl)-1H-1,2,4-triazole-5(4H)-thione - Fun, Hoong-Kun (International Union of Crystallography, 2009)
In the title triazole compound, C(10)H(12)N(4)OS, the triazole ring is essentially planar [maximum deviation = 0.009 (1) Å] and forms a dihedral angle of 5.78 (4)° with the benzene ring. In the crystal structure, molecules are linked into dimers by centrosymmetric N—H⋯S interactions. These dimers are linked into two-molecule-wide tapes by N—H⋯N and S⋯S [3.2634 (3) Å] interactions. In addition, they are further interconnected by weak N—H⋯S interactions into sheets parallel to the ab plane. The crystal structure is further stabilized by weak intermolecular C—H⋯π interactions.